A closer look at heart failure in patients with concurrent diabetes mellitus using glucose lowering drugs. Issue 1 (2nd January 2019) - Shah, Syed Raza; Iqbal, Sana Muhammad; Alweis, Richard; Roark, Steven
ABSTRACT: Introduction : Type 2 diabetes (T2D) is an independent risk factor for heart failure (HF). With concomitant T2D and HF, recent data suggests an incremental risk of cardiovascular death and hospitalization for HF, as compared to patients with HF without T2D. Areas covered : Management of these two diseases has been a challenge for physicians. The treatment goals for HF patients in T2D are very important. They serve as the endpoint in using a specific treatment for management and treatment of T2D patients hence, decreasing mortality rates. In this review, we examine the effects of oral antidiabetic drugs on HF patients, discussing current evidence-based up-to-date management strategies and guidelines in the general population with HF and T2D. Expert commentary : Future in the management of T2D in HF patients looks bright. Augmenting data on potential cardiovascular side effects of antidiabetic drugs is valuable since millions of people are treated over many years. Newer novel drugs targeting specific signaling pathways are approaching the stages of clinical investigation. They have been a highly attractive concept for the future in the management of these patients. However, while advances in technology elucidated many aspects of these diseases, many mysteries still remain.